Pola Asuh Asisten Rumah Tangga Terhadap Pembentukan Karakter Anak (Studi Pada Asisten Rumah Tangga di Gampong Seuriget) - Mawaddah Rizki; Itryah (Teaching and Learning Journal of Mandalika (Teacher) e- ISSN 2721-9666, 2024)
This research aims to find out how the parenting patterns of household assistants influence the formation of children's character and what factors influence the parenting patterns of household assistants on the formation of children's character in Gampong Seuriget, Langsa City, Aceh. In this case, the researcher only limited the research to the parenting patterns of household assistants with the aim of knowing the formation of children's character. This research uses the format of a qualitative research design, namely a qualitative descriptive design and uses a phenomenological approach to understand the parenting patterns of household assistants on the formation of children's character. In this research, the researcher used 6 sources, 2 as research subjects, 2 as informants for the perpetrators of each subject and 2 others as informed informants. Based on the results of the analysis carried out by researchers, it can be concluded that there are broad similarities regarding the psychological dynamics carried out on the subjects of this research which give rise to several aspects of parenting patterns and factors that influence the parenting patterns of household assistants on the formation of children's character so that they form values. character values of honesty, creativity, religiousness, tolerance, discipline, independence, high curiosity, democracy, caring about the social environment and also responsibility.